Leadership, LMX and teaching process quality in primary schools - Ivan Tasić; Miroljub Merdović; Jelena Jankov; Milan Nikolić; Edit Terek; Zoran Jovanović (Anali Ekonomskog fakulteta u Subotici, 2020)
The aim of the research in this paper is to examine the direction and intensity of the influence of leadership in schools and the LMX relationship on the teaching process, and the personal and ethical development of pupils. The survey was conducted by means of a questionnaire, and the respondents were teachers in elementary schools in Serbia. A total of 406 valid questionnaires were collected. The average scores of leadership, LMX relationships, the teaching process and pupils’ development are high. Transformational leadership is more pronounced than transactional leadership. All the dimensions of leadership, as well as all the aspects of the LMX relationship, have a statistically significant and positive influence on the teaching process, as well as the ethical and personal development of pupils. The strongest influence of leadership and the LMX relation on the dimensions of the teaching process occurs for those dimensions which include activities outside the classroom, while the weakest impact on the teaching process dimensions exists for those dimensions directly related to teaching activities over time. Principals should be more interested in the work of individual teachers and provide them with appropriate feedback. In general, principals should continuously work to improve leadership and LMX relationships.